Developing Discipline And Responsibility Character In Elementary School Students - Nensi Desiana Purnamasari; Kayla Hajar Zahira; Murfiah Dewi Wulandari; Darsinah Darsinah (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study synthesizes empirical evidence on the development of discipline and responsibility character among elementary school students using a Systematic Literature Review (SLR) based on the PRISMA 2020 framework. The review analyzed 15 articles selected from 120 records retrieved from Google Scholar (2021–2026). Data were examined through thematic coding and narrative synthesis. The findings indicate that discipline and responsibility character are shaped by multiple interrelated factors, including the role of teachers, active learning strategies such as Problem-Based Learning (PBL) and Numbered Heads Together (NHT), habituation through school rules, school environment, parenting, extracurricular activities, and character assessment practices. The results also show that character development occurs gradually through continuous and collaborative efforts among teachers, parents, and schools. These findings highlight that character formation in elementary education is a complex and multi-factor process with important implications for educational practice and future research.